ESG performance, investors’ heterogeneous beliefs, and cost of equity capital in China - Tang, Hua (Frontiers in Environmental Science, 2022)
Abstract:Previous studies on the relationship between environmental, social and governance (ESG) information disclosure and cost of equity (COE) have found mixed results.They conclude that this relationship may be affected by some attributes of the company inside.In this study, we examine whether investors'heterogeneous beliefs moderates the relationship between ESG performance and COE. Our sample starts with ESG-rating firms included in Huazheng index of the Wind China financial database(WIND) for years 2015 to 2020.We collect financial information and relevant data from the China Stock Market and Accounting Research database(CSMAR).Using a two-way fixed effect multiple regression model, we report a negative moderate effect of both ESG performance on COE. We also find that COE Is higher when the firm financing constraints increase. investors'heterogeneous beliefs with a lower (rather than higher) level tends to pay close attention from ESG performance by stakeholders and financing constraints decreases, which then leads to the reduction of investors' expected risk.We therefore conclude that firms that manage actions on ESG issues have a better choices of release investors disagreements which in turn reduces their equity financing costs.